2022
DOI: 10.3390/ijerph191912964
|View full text |Cite
|
Sign up to set email alerts
|

Leaving Past Adversities Behind: Gratitude Intervention Compensates for the Undesirable Effects of Past Time Perspectives on Negative Affect

Abstract: Both gratitude and savoring the moment are considered to be well-established “well-being boosters” (WBBs). Each of them has a salient temporal reference: Gratitude is past-related, whereas savoring the moment refers to the present. The temporal match–mismatch model posits that time perspectives (TPs) moderate the effects of WBBs on well-being if they refer to the same temporal frame (e.g., gratitude and Past-Positive). Our study tested whether TPs moderate the effects of two positive interventions on positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…In the model analyzed in this study, grateful disposition had a considerable influence on positive interpretation, except for the influence of social support. This result supports the view that thinking positively is related to practicing gratitude, without support from others and when undesirable things happen [ 16 ]. This viewpoint is also supported by the finding that the path from gratitude disposition to subjective happiness in young adults through positive interpretation was significant in the mediating model.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the model analyzed in this study, grateful disposition had a considerable influence on positive interpretation, except for the influence of social support. This result supports the view that thinking positively is related to practicing gratitude, without support from others and when undesirable things happen [ 16 ]. This viewpoint is also supported by the finding that the path from gratitude disposition to subjective happiness in young adults through positive interpretation was significant in the mediating model.…”
Section: Discussionsupporting
confidence: 85%
“…Burzynska-Tatjewska and Stolarski found that changing people’s perspectives on undesirable past events, which trigger negative emotions, by practicing gratitude can make them happier and improve their well-being [ 16 ]. In other words, people can be happier if they positively modify their interpretation of past experiences.…”
Section: Introductionmentioning
confidence: 99%